2015
DOI: 10.1039/c5cc04323a
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel 2D cadmium(ii)-MOF in the formation of a photo-switch with a substantial on–off ratio

Abstract: A novel thiocyanate bridged 2D MOF, [CdL(μ-1,3-SCN)2]n, [HL = 2-(2-(ethylamino)ethyliminomethyl)-6-ethoxyphenol] has been synthesized and characterized by X-ray crystallography. The band gap of the synthesized material in the solid state has been determined by experimental measurements and compared with the theoretical value obtained from DFT calculations. For the first time, the single crystal X-ray crystallography of a MOF has been reported along with its applicability in photosensitive devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 28 publications
(46 reference statements)
0
46
0
Order By: Relevance
“…4 Due to their high surface area, uniform yet tunable porosity, and rich chemical functionality, enormous attempts have been made for the synthesis of MOFs with a new structure with novel topology and potential applications in the emerging fields of storage, separation, sensing, catalysis, optoelectronic devices, etc. 511 The promising class of MOF has strongly promoted the research of hybrid organic–inorganic solids comprising the association of metallic centers with organic O- and/or N-donor ligands for the formation of novel crystalline periodic networks. 12,13 Syntheses of MOFs are influenced by various factors such as the reaction conditions that include nature of anions, coordination geometry of the central atom, temperature, solvent, and flexibility of the organic ligands, either singly or multiply.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Due to their high surface area, uniform yet tunable porosity, and rich chemical functionality, enormous attempts have been made for the synthesis of MOFs with a new structure with novel topology and potential applications in the emerging fields of storage, separation, sensing, catalysis, optoelectronic devices, etc. 511 The promising class of MOF has strongly promoted the research of hybrid organic–inorganic solids comprising the association of metallic centers with organic O- and/or N-donor ligands for the formation of novel crystalline periodic networks. 12,13 Syntheses of MOFs are influenced by various factors such as the reaction conditions that include nature of anions, coordination geometry of the central atom, temperature, solvent, and flexibility of the organic ligands, either singly or multiply.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the performance of the devices, detailed analysis of the charge-transport properties is also of extreme significance. 911…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] For example, our group has reported cadmium(II) and copper(II) based coordination polymers, both showing photosensitivity with subsequent on/off ratio. 10,11 Any semiconducting material showing a rectifying nature in metal-semiconductor junction may be used to fabricate a Schottky diode, which is a wellknown opto-electronic device. Ghoshal et al reported a cadmium(II) based metal organic framework that can behave as a Schottky barrier diode.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of N, O‐donor ligands by Schiff base condensation reaction is popular amid scientists. Most of the transition metal complexes with Schiff base ligands have been developed in a number of necessary fields of applications, for example, magnetism, optoelectronics, biological sciences, catalysis, sensing, etc. On the other hand, because of the strong coordination behaviour and high biological activity, some of the Schiff base complexes derived from amino acids have become a hot research topic for years .…”
Section: Introductionmentioning
confidence: 99%